2014
DOI: 10.1007/s10637-014-0094-5
|View full text |Cite
|
Sign up to set email alerts
|

Phase I and pharmacokinetic study of trabectedin, a DNA minor groove binder, administered as a 24-h continuous infusion in Japanese patients with soft tissue sarcoma

Abstract: SummaryBackground Trabectedin is a novel anticancer agent used to treat soft tissue sarcoma (STS). This phase I study of trabectedin was performed to determine the recommended dose for phase II studies in Japanese patients with STS. Methods Patients who had STS refractory to, or who could not tolerate, anthracycline-based chemotherapy were enrolled. The starting dose of trabectedin was 0.9 mg/m2, given as a 24-h continuous infusion every 21 days. The dose was escalated to 1.2 mg/m2 and then to 1.5 mg/m2, using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…The approved dose in Japan is based on the results of a phase I study in Japanese advanced STS patients who had received treatment with at least one anthracycline-based regimen [21]. Dose-limiting toxicity was experienced by two of three patients who received trabectedin at a dose of 1.5 mg/m 2 ; one had grade 3 increased creatine phosphokinase and grade 3 anorexia, and the other had grade 4 decreased platelet count.…”
Section: Resultsmentioning
confidence: 99%
“…The approved dose in Japan is based on the results of a phase I study in Japanese advanced STS patients who had received treatment with at least one anthracycline-based regimen [21]. Dose-limiting toxicity was experienced by two of three patients who received trabectedin at a dose of 1.5 mg/m 2 ; one had grade 3 increased creatine phosphokinase and grade 3 anorexia, and the other had grade 4 decreased platelet count.…”
Section: Resultsmentioning
confidence: 99%
“…Patients with histologically proven translocation‐related sarcoma and who previously received standard therapy were included 6 . In all patients, trabectedin was administered at a dosage of 1.2 mg/m 2 every 3 weeks according to the results of the preceding phase I study conducted in Japan 7 . Trabectedin treatment was delayed until the following criteria were met; neutrophil count more than 1500 cells per μL, platelet count more than 10 × 10 4 cells per μL, blood albumin more than 2.5 g/dL, total bilirubin less than 1.5 mg/dL, aspartate aminotransferase (AST), alanine aminotransferase (ALT), and creatine phosphokinase (CPK) less than 2.5 times of upper limit of normal, and creatinine clearance more than 30 mL per minutes.…”
Section: Methodsmentioning
confidence: 99%
“…13 In Japan, a phase 1 pharmacokinetic study of trabectedin administered to patients with advanced STS resulted in a recommended dose of 1.2 mg/m 2 as a 24-hour continuous infusion, which differs from the recommended dose of 1.5 mg/m 2 as a 24-hour continuous infusion in the United States and Europe. 14 In this dose setting, a phase 2, randomized, open-label study revealed the efficacy of trabectedin in comparison with best supportive care in patients with advanced TRS after standard chemotherapy. 6 In 2015, on the basis of this result, trabectedin was approved in Japan for the treatment of all histological types of STS.…”
Section: Introductionmentioning
confidence: 99%